Composite positive plate

By using the composite structure of polycrystalline lithium manganate and monocrystalline lithium manganate in the positive chip of lithium manganate batteries, and adding binders to the lithium mangan lithium manganate layer to solve the problem of attenuation of lithium manganate battery capacity attenuation , Improve the circulation performance and energy density of the battery.

CN119381399AInactive Publication Date: 2025-01-28SHANGHAI SAIC QINGTAO ENERGY TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411498701.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The capacity of lithium manganate batteries will gradually decay during the cycle, mainly due to the disproportionation reaction caused by Mn3+ and the dissolution of manganese ions.

Method used

The composite positive chip structure is adopted. Among them, the first positive active material layer is composed of polycrystalline lithium manganate, and the second positive active activity material layer is composed of monocrystalline lithium manganate. Manganese ion.

Benefits of technology

By reducing the dissolution and migration of manganese ions, the capacity attenuation caused by the reorganization of the SEI membrane is eased, and the circulation performance and energy density of lithium manganate batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to a composite positive plate in the technical field of lithium batteries. The composite positive plate comprises a current collector, a first positive active material layer and a second positive active material layer, the first positive active material layer is arranged on at least one surface of the current collector, and the second positive active material layer is arranged on the surface, away from the current collector, of the first positive active material layer; the first positive electrode active material layer comprises a first positive electrode active material, and the second positive electrode active material layer comprises a second positive electrode active material; wherein the first positive electrode active material is polycrystalline lithium manganate; and the second positive electrode active material is monocrystal lithium manganate. The single-crystal lithium manganate is arranged on one side, far away from the current collector, of the polycrystal lithium manganate, so that manganese ions separated from the first positive active material layer are intercepted, dissolution of the manganese ions is reduced, the Mn ions migrated from the composite positive plate to a negative electrode are reduced to a certain extent, capacity fading caused by SEI membrane recombination is relieved, and the service life of the composite positive plate is prolonged. And the cycle performance of the lithium manganate battery is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a composite positive electrode sheet. Background Art

[0002] With the development and progress of science and technology, lithium-ion batteries are increasingly widely used in power, energy storage, 3C and other fields. The market has higher and higher requirements for the energy density of lithium-ion batteries. The use of high-energy-density positive and negative electrodes, reducing the proportion of inactive substances and thick electrodes have become the main development direction in this field. Lithium manganese oxide, as a good positive electrode material for lithium-ion batteries, is widely used in the field. However, the problem with lithium manganese oxide batteries is that the battery capacity will gradually decay as the battery cycles.

[0003] It is generally recognized in the art that the capacity decay of LiMn2O4 during the cycle process is mainly caused by Mn 3+ Since the electrolyte contains a small amount of water, the water reacts with the LiPF6 in the electrolyte to generate HF, which causes the spinel LiMn2O4 to undergo a disproportionation reaction. 3+ Disproportionation reaction occurs to generate Mn 2+ and Mn 4+ , Mn 2+ Mn will dissolve at high temperatures. 2+ The dissolution rate of LiMn2O4 increases, causing the structure of LiMn2O4 to be destroyed; during the charging process, Mn 2+ Migrate to the negative electrode, resulting in the reorganization of the SEI film and thus causing capacity decay.

[0004] In order to solve the problem that the battery capacity of lithium manganese oxide batteries is easily attenuated, the present invention proposes a composite positive electrode sheet. Summary of the invention

[0005] In order to solve the above technical problems, the present invention discloses a composite positive electrode sheet, and the technical solution of the present invention is implemented as follows:

[0006] A composite positive electrode sheet, comprising a current collector, a first positive electrode active material layer and a second positive electrode active material layer;

[0007] The first positive electrode active material layer is disposed on at least one surface of the current collector, and the second positive electrode active material layer is disposed on a surface of the first positive electrode active material layer away from the current collector;

[0008] The first positive electrode active material layer comprises a first positive electrode active material, and the second positive electrode active material layer comprises a second positive electrode active material;

[0009] Wherein, the first positive electrode active material is polycrystalline lithium manganese oxide; and the second positive electrode active material is single crystal lithium manganese oxide.

[0010] Preferably, the first positive electrode active material layer has a gram capacity of 120 mAh / g to 130 mAh / g;

[0011] The second positive electrode active material layer has a gram capacity of 90 mAh / g to 100 mAh / g.

[0012] Preferably, the thickness of the first positive electrode active material layer is 60% to 80% of the composite positive electrode sheet.

[0013] The thickness of the second positive electrode active material layer is 15% to 38% of the composite positive electrode sheet.

[0014] Preferably, the polycrystalline lithium manganate D50 ranges from 6.0 μm to 18.0 μm;

[0015] The D50 range of the single crystal lithium manganese oxide is 4.0 μm to 18.0 μm.

[0016] Preferably, the second positive electrode active material layer further comprises a binder;

[0017] The binder contains hydroxyl groups and / or carboxyl groups in its molecular formula.

[0018] Preferably, the binder comprises PAA and / or PAN.

[0019] Preferably, it also includes a composite electrolyte layer;

[0020] The composite electrolyte layer is disposed on a surface of the second positive electrode active material layer away from the first positive electrode active material layer;

[0021] The composite electrolyte layer comprises nanofibers and a solid electrolyte;

[0022] The nanofibers are uniformly dispersed in the composite electrolyte layer.

[0023] Preferably, the nanofibers include polyacrylonitrile fibers modified by -NH2 grafting.

[0024] Preferably, the solid electrolyte is water-soluble polyurethane;

[0025] The water-soluble polyurethane and the polyacrylonitrile fiber are combined by dispersing the polymer solution and the polyacrylonitrile fiber after blending.

[0026] Preferably, the composite electrolyte layer further comprises a lithium salt;

[0027] The ionic conductivity of the composite electrolyte layer is (6.0)×10-5S·cm -1 ;

[0028] The thickness of the composite electrolyte layer is 2% to 5% of the thickness of the composite positive electrode sheet.

[0029] In the technical solution of the present invention, the first positive electrode active material in the first positive electrode active material layer close to the current collector is polycrystalline lithium manganese oxide, which can ensure the energy density of the battery; in addition, a second positive electrode active material layer containing single-crystalline lithium manganese oxide is arranged on the side of the first active material layer away from the current collector. Single-crystalline lithium manganese oxide has a smaller specific surface area and is not prone to manganese dissolution. The technical solution of the present invention arranges the second positive electrode active material layer containing single-crystalline lithium manganese oxide material on the side of the polycrystalline lithium manganese oxide (that is, the first positive electrode active material layer) away from the current collector, which can intercept the manganese ions precipitated from the first positive electrode active material layer, reduce the dissolution of manganese ions, and reduce the Mn ions migrating from the composite positive electrode sheet to the negative electrode to a certain extent, thereby helping to alleviate the capacity decay caused by SEI film reorganization and ensure the cycle performance of the lithium manganese oxide battery. DETAILED DESCRIPTION

[0030] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the description and claims of the present invention and the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.

[0032] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0033] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.

[0034] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects before and after are in an "or" relationship.

[0035] Throughout the present invention, numerical values ​​represent approximate measures or limits of ranges to cover minor deviations from given values ​​as well as embodiments with about the values ​​mentioned and embodiments with the exact values ​​mentioned. Except for the working examples provided at the end of the detailed description, all numerical values ​​of parameters (e.g., amounts or conditions) in this specification (including the appended claims) should be understood to be modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. "About" indicates that the stated numerical value allows some minor imprecision (close to the exact value of the value to some extent; approximately or reasonably close to the value; almost). If the imprecision provided by "about" is not otherwise understood in this ordinary sense in the art, "about" as used in the present invention at least indicates the variation that can be produced by the ordinary methods of measuring and using such parameters. For example, "about" may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some aspects, optionally less than or equal to 0.1%.

[0036] Additionally, disclosure of ranges includes disclosure of all values ​​within the entire range and further divided ranges, including endpoints and sub-ranges given for such ranges.

[0037] The present invention provides a composite positive electrode sheet, which comprises a current collector, a first positive electrode active material layer and a second positive electrode active material layer;

[0038] The first positive electrode active material layer is disposed on at least one surface of the current collector, and the second positive electrode active material layer is disposed on a surface of the first positive electrode active material layer away from the current collector;

[0039] The first positive electrode active material layer comprises a first positive electrode active material, and the second positive electrode active material layer comprises a second positive electrode active material;

[0040] Wherein, the first positive electrode active material is polycrystalline lithium manganese oxide; and the second positive electrode active material is single crystal lithium manganese oxide.

[0041] In the present invention, the active material of the first positive electrode active material layer is polycrystalline lithium manganate, which is a secondary particle formed by a large number of primary particle clusters. Compared with single-crystal lithium manganate, polycrystalline lithium manganate has a large specific surface area. Setting it as the first positive electrode active material can increase the specific surface area of ​​the first positive electrode active material layer, thereby increasing the side reactions on the surface, making it easier for the first positive electrode active material layer to precipitate Mn ions; the active material of the second positive electrode active material layer is single-crystal lithium manganate, which has a smaller specific surface area and is not easy to dissolve manganese. The technical solution of the present invention sets the second positive electrode active material layer of the single-crystal lithium manganate material on the side away from the current collector of the polycrystalline lithium manganate (that is, the first positive electrode active material layer), thereby intercepting the manganese ions precipitated from the first positive electrode active material layer, reducing the dissolution of manganese ions, and reducing the Mn ions migrating from the composite positive electrode sheet to the negative electrode to a certain extent, thereby helping to alleviate the capacity decay caused by the recombination of the SEI film and ensuring the cycle performance of the lithium manganate battery.

[0042] In some embodiments, the first positive electrode active material layer has a gram capacity of 120 mAh / g to 130 mAh / g; and the second positive electrode active material layer has a gram capacity of 90 mAh / g to 100 mAh / g.

[0043] In some preferred embodiments, the thickness of the first positive electrode active material layer is 60% to 80% of the composite positive electrode sheet.

[0044] In actual applications, the specific options are 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, and 80%. The above values ​​are only examples and are not limiting.

[0045] In some preferred embodiments, the thickness of the second positive electrode active material layer is 15% to 38% of the composite positive electrode sheet.

[0046] In practical applications, you can choose 15%, 16%, 17%, 18%, 19%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36% or 38%, etc. The above values ​​are only examples and are not limiting.

[0047] Through the above arrangement, the first positive electrode active material layer with polycrystalline lithium manganese oxide has a higher gram capacity, and the thickness is greater than that of the second positive electrode active material layer, which can ensure the overall energy density of the battery. In addition, a second positive electrode active material layer containing single-crystal lithium manganese oxide is arranged on the side of the first positive electrode active material layer away from the current collector. On the one hand, compared with the positive electrode sheet prepared entirely with polycrystalline lithium manganese oxide, the content of polycrystalline lithium manganese oxide that is easy to precipitate manganese ions is reduced; on the other hand, the manganese ions precipitated from the first positive electrode active material layer can be intercepted, the manganese ions that are easy to dissolve can be reduced, and the Mn ions migrating to the negative electrode can be reduced to a certain extent, and the SEI film reorganization can be further alleviated to cause the capacity attenuation, thereby ensuring the cycle performance of the lithium manganese oxide battery.

[0048] In some more preferred embodiments, the D50 range of the polycrystalline lithium manganese oxide is 6.0 μm to 18.0 μm; the D50 range of the single crystal lithium manganese oxide is 4.0 μm to 18.0 μm.

[0049] In the present invention, the first positive electrode active material layer has a high gram capacity, which can provide a high capacity for the battery. In the second positive electrode active material layer, the single crystal lithium manganese oxide has fewer grain boundaries, which ensures the electronic conductivity of the positive electrode sheet; and the single crystal lithium manganese oxide is not easy to dissolve manganese ions, which can reduce the Mn ions migrating to the negative electrode while ensuring the battery capacity, thereby ensuring the battery performance.

[0050] In some embodiments, the first positive electrode active material layer further includes a first binder and a first conductive agent. It is understood that the first binder is a material used to bind the first active material, the first conductive agent and other components together. Without violating the inventive concept of the present application, the present application also has no special requirements for the type of the first binder, and any known binder type can be used in the second active material layer.

[0051] The first binder includes any one of polytetrafluoroethylene, polyvinylidene fluoride, polypropylene, polyethylene, styrene-butadiene rubber, nitrile rubber, sodium hydroxymethyl cellulose, polyacrylic acid, polyacrylonitrile or sodium alginate, or a combination of at least two thereof.

[0052] It is understood that the first conductive agent is mainly used to assist and improve the conductivity in the secondary battery. There is no particular limitation on the first conductive agent in the present application, as long as it has electronic conductivity without causing chemical changes. Specifically, the first conductive agent includes any one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers, or a combination of at least two thereof.

[0053] In some embodiments, the second positive electrode active material layer further includes a binder; the molecular formula of the binder includes a hydroxyl group and / or a carboxyl group.

[0054] In the present invention, in addition to playing the role of the binder itself, the binder contains a large number of hydroxyl groups and carboxyl groups in its molecular structure, which can provide a large number of active sites and interact with manganese ions in various ways such as coordination, chelation, and hydrogen bonding. In addition, the hydroxyl groups and manganese ions have a high affinity, and the two can achieve over-coordination bonding, so that the binder also has the function of capturing manganese ions, thereby enhancing the interception effect of the second positive electrode active material layer on the manganese ions dissolved from the first positive electrode active material layer, thereby improving the performance of the lithium manganese oxide battery.

[0055] In some preferred embodiments, the binder includes PAA and / or PAN.

[0056] In practical applications, the binder can be PAA, PAN, or a mixture of PAA and PAN, and the present invention does not impose any limitation thereto. In addition, other binders having the same or similar properties as PAA or PAN can also be used.

[0057] In some embodiments, the second positive electrode active material layer further includes a second conductive agent, which is also not particularly limited in the present application as long as it has electronic conductivity without causing chemical changes. Specifically, the second conductive agent can be the same as or different from the first conductive agent.

[0058] In one embodiment, the second conductive agent may independently include graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers, such as carbon fibers and metal fibers; conductive tubes, such as carbon nanotubes; metal powders, such as fluorocarbon powders, aluminum powders, and nickel powders; conductive whiskers, such as zinc oxide and potassium titanate; conductive metal oxides, such as titanium oxide; and polyphenylene derivatives, and preferably includes carbon black from the aspect of improving conductivity.

[0059] In some embodiments, the composite cathode sheet further includes a composite electrolyte layer;

[0060] The composite electrolyte layer is disposed on a surface of the second positive electrode active material layer away from the first positive electrode active material layer;

[0061] The composite electrolyte layer comprises nanofibers and a solid electrolyte;

[0062] The nanofibers are uniformly dispersed in the composite electrolyte layer.

[0063] Nanofibers can prevent the dissolution of metal ions in the composite positive electrode after long-term battery cycling.

[0064] It is understandable that the present application does not impose any specific limitation on nanofibers, and any nanofibers that can adsorb transition metal ions can be used as the nanofibers in the present application.

[0065] The nanofibers may be polymer nanofibers or inorganic compound nanofibers.

[0066] In some embodiments, the nanofibers include polyacrylonitrile fibers. Polyacrylonitrile fibers can effectively prevent manganese ions from dissolving into the negative electrode during long-term cycling of the battery cell, thereby causing capacity decay. Specifically, the polyacrylonitrile fibers can effectively adsorb transition metal ions. More specifically, the cyano group of polyacrylonitrile can generate electrostatic attraction to transition metal ions.

[0067] The polymers used to prepare polymer nanofibers include polyacrylonitrile (PAN), cellulose acetate, polyvinylidene fluoride (PVDF), polypropylene (PP), polyether sulfone (PES) and polysulfone (PSF).

[0068] The inorganic compounds used to prepare the inorganic compound nanofibers include alumina, zirconia, silica, titania and the like.

[0069] In a specific embodiment, the nanofibers are porous structures.

[0070] In some embodiments, the nanofibers include polyacrylonitrile fibers modified by -NH2 grafting.

[0071] In the present invention, the modified polyacrylonitrile fiber can effectively improve the adsorption capacity of the second positive electrode active material layer for manganese ions, thereby achieving a further interception effect on manganese ions.

[0072] In some embodiments, the solid electrolyte is a water-soluble polyurethane;

[0073] The water-soluble polyurethane and the polyacrylonitrile fiber are combined by dispersing the polymer solution and the polyacrylonitrile fiber after blending.

[0074] In the present invention, the water-soluble polyurethane can dissolve a large amount of lithium salt and has good flexibility, can provide good ion conductivity, and also has good mechanical strength and thermal stability, further improving the safety performance of the battery cell.

[0075] As an embodiment, when the solid electrolyte contained in the composite electrolyte layer is a water-soluble polyurethane, it also includes a solid plasticizer, and the solid plasticizer can be substantially miscible in the overall structure of the waterborne polyurethane. The present application has no special requirements for the type of plasticizer. On the basis of not violating the inventive concept of the present application, all known types of plasticizers suitable for waterborne polyurethane can be used in the present application; as an illustrative example only, at least one solid plasticizer can include an organic material (e.g., a small solid organic molecule) and / or an oligomeric polymer material; for example, the at least one solid plasticizer can be selected from glutaronitrile, succinonitrile, adiponitrile, fumaronitrile and a combination thereof.

[0076] Optionally, the water-soluble polyurethane and the polyacrylonitrile fiber account for 20wt% to 35wt% of the composite electrolyte layer. In practical applications, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt%, 30wt%, 32wt% or 35wt% can be selected, and the above values ​​are only examples and are not limited.

[0077] In some preferred embodiments, the composite electrolyte layer further comprises a lithium salt. The present application does not particularly limit the type of lithium salt, and any known type of lithium salt can be used in the present application without violating the inventive concept of the present application. Under the action of the water-soluble polyurethane and the lithium salt, lithium ions can smoothly pass through the composite electrolyte layer.

[0078] As an illustrative example only, and not a limitation of the scope of protection, the lithium salt can be lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrachloroaluminate (LiAlCl4), lithium iodide (LiI), lithium bromide (LiBr), lithium thiocyanate (LiSCN), lithium tetrafluoroborate (LiBF4), lithium difluorooxalatoborate (LiBF2(C2O4))(LiODFB), lithium tetraphenylborate (LiB(C6H5)4), lithium bis(oxalate)borate (LiB(C2O4)2)(LiBOB), lithium tetrafluorooxalatophosphate (LiPF4(C2O4))(LiFOP), lithium nitrate (LiNO3), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonyl imide) (LITFSI)(LiN(CF3SO2)2), lithium bis(fluorosulfonyl imide) (LiN(FSO2)2)(LIFSI) and combinations thereof. In some embodiments, the lithium salt is selected from one or more of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethanesulfonyl imide) (LiTFSI)(LiN(CF3SO2)2), lithium bis(fluorosulfonyl imide) (LiN(FSO2)2)(LiFSI), lithium fluoroalkyl phosphonate (LiFAP), and lithium phosphate (Li3PO4).

[0079] As an embodiment, the lithium salt content in the composite electrolyte layer is 10-60wt%, for example, 10wt%, 15wt%, 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt% or 60wt%, etc.; it can be understood that there is no special requirement for the lithium salt content, and it is known in the art to adjust the ionic conductivity of the solid electrolyte layer by the lithium salt content.

[0080] In some preferred embodiments, the ionic conductivity of the composite electrolyte layer is (6.0-7.0)×10 - 5 S cm -1 . For example, 6.0×10-5S·cm-1, 6.1×10-5S·cm-1, 6.2×10-5S·cm-1, 6.3×10-5S·cm-1, 6.4×10-5S·cm-1, 6.5×10-5S·cm-1, 6.6×10-5S·cm-1, 6.7×10-5S·cm-1, 6.8×10-5S·cm-1, 6.9×10-5S·cm-1, 7.0×10-5S·cm-1, etc., and I will not list them all here.

[0081] In some preferred embodiments, the thickness of the composite electrolyte layer is 2% to 5% of the thickness of the composite positive electrode sheet. In practical applications, 2%, 3%, 4% or 5% may be selected. The above values ​​are only examples and are not limiting.

[0082] In some embodiments, the composite electrolyte layer also includes a third binder, which includes polyethylene glycol, polyethylene oxide (PEO), poly(p-phenylene ether) (PPO), poly(methyl methacrylate) (PMMA), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyvinyl chloride (PVC), and combinations thereof. The third binder can be selected according to actual needs without violating the inventive concept of the present application, and is not specifically limited here.

[0083] The embodiments of the present invention will be described in more detail below by way of examples. It should be noted that the embodiments of the present invention are not limited to these examples.

[0084] Example 1

[0085] A composite positive electrode sheet includes a current collector and a first positive electrode active material layer and a second positive electrode active material layer sequentially arranged on the surface of the current collector.

[0086] The first positive electrode active material layer is composed of 96wt% polycrystalline lithium manganese oxide, 2wt% acetylene black and 2wt% PVDF, with a gram capacity of 120mAh / g, a thickness of 90μm, and a polycrystalline lithium manganese oxide D50 of 15μm;

[0087] The second positive electrode active material layer is composed of 96wt% single crystal lithium manganese oxide, 2wt% acetylene black, 2wt% PAA and PAN mixture, with a gram capacity of 100mAh / g, a thickness of 10μm, and a single crystal lithium manganese oxide D50 of 5μm.

[0088] Example 2

[0089] A composite positive electrode sheet comprises a current collector and a first positive electrode active material layer and a second positive electrode active material layer sequentially arranged on the surface of the current collector.

[0090] The first positive electrode active material layer is composed of 96wt% polycrystalline lithium manganese oxide, 2wt% acetylene black and 2wt% PVDF, with a gram capacity of 120mAh / g, a thickness of 80μm, and a polycrystalline lithium manganese oxide D50 of 15μm;

[0091] The second positive electrode active material layer is composed of 96wt% single crystal lithium manganese oxide, 2wt% acetylene black, 2wt% PAA and PAN mixture, with a gram capacity of 100mAh / g, a thickness of 20μm, and a single crystal lithium manganese oxide D50 of 5μm.

[0092] Compared with Example 1, the thickness of the first positive electrode active material layer of this example is reduced, and the thickness of the second positive electrode active material layer is increased.

[0093] Example 3

[0094] A composite positive electrode sheet includes a current collector and a first positive electrode active material layer, a second positive electrode active material layer, and a composite electrolyte layer arranged on the outer side of the second positive electrode active material layer in sequence on the surface of the current collector.

[0095] The first positive electrode active material layer is composed of 96wt% polycrystalline lithium manganese oxide, 2wt% acetylene black and 2wt% PVDF, with a gram capacity of 120mAh / g, a thickness of 75μm, and a polycrystalline lithium manganese oxide D50 of 15μm;

[0096] The second positive electrode active material layer is composed of 96wt% single crystal lithium manganese oxide, 2wt% acetylene black, 2wt% PAA and PAN mixture, with a gram capacity of 100mAh / g, a thickness of 25μm, and a single crystal lithium manganese oxide D50 of 5μm.

[0097] Example 4

[0098] A composite positive electrode sheet includes a current collector and a first positive electrode active material layer, a second positive electrode active material layer, and a composite electrolyte layer arranged on the outer side of the second positive electrode active material layer in sequence on the surface of the current collector.

[0099] The first positive electrode active material layer is composed of 96wt% polycrystalline lithium manganese oxide, 2wt% acetylene black and 2wt% PVDF, with a gram capacity of 120mAh / g, a thickness of 80μm, and a polycrystalline lithium manganese oxide D50 of 15μm;

[0100] The second positive electrode active material layer is composed of 96wt% single crystal lithium manganese oxide, 2wt% acetylene black and 2wt% PAA and PAN mixture, with a gram capacity of 100mAh / g, a thickness of 15μm, and a single crystal lithium manganese oxide D50 of 5μm;

[0101] The composite electrolyte layer includes 3 wt% polyacrylonitrile fiber, 27 wt% water-soluble polyurethane and 10 wt% LiClO4, with an electrical conductivity of (6.0)×10-5S·cm-1 and a thickness of 5 μm.

[0102] Example 5

[0103] A composite positive electrode sheet comprises a current collector and a first positive electrode active material layer and a second positive electrode active material layer sequentially arranged on the surface of the current collector.

[0104] The first positive electrode active material layer is composed of 96wt% polycrystalline lithium manganese oxide, 2wt% acetylene black and 2wt% PVDF, with a gram capacity of 120mAh / g, a thickness of 80μm, and a polycrystalline lithium manganese oxide D50 of 15μm;

[0105] The second positive electrode active material layer is composed of 96wt% single crystal lithium manganese oxide, 2wt% acetylene black, and 2wt% PVDF, with a gram capacity of 100mAh / g, a thickness of 20μm, and a single crystal lithium manganese oxide D50 of 5μm.

[0106] Compared with Example 2, the binder of the second positive active material layer of this example is changed from 2 wt % of the mixture of PAA and PAN to 2 wt % of PVDF.

[0107] Example 6

[0108] A composite positive electrode sheet includes a current collector and a first positive electrode active material layer, a second positive electrode active material layer, and a composite electrolyte layer arranged on the outer side of the second positive electrode active material layer in sequence on the surface of the current collector.

[0109] The first positive electrode active material layer is composed of 96wt% polycrystalline lithium manganese oxide, 2wt% acetylene black and 2wt% PVDF, with a gram capacity of 120mAh / g, a thickness of 60μm, and a polycrystalline lithium manganese oxide D50 of 15μm;

[0110] The second positive electrode active material layer is composed of 96wt% single crystal lithium manganese oxide, 2wt% acetylene black and 2wt% PAA and PAN mixture, with a gram capacity of 100mAh / g, a thickness of 38μm, and a single crystal lithium manganese oxide D50 of 5μm;

[0111] The composite electrolyte layer includes 3 wt% polyacrylonitrile fiber, 27 wt% water-soluble polyurethane and 10 wt% LiClO4, with an electrical conductivity of (6.0)×10-5S·cm-1 and a thickness of 2 μm.

[0112] Comparative Example 1

[0113] A composite positive electrode sheet comprises a current collector and a first positive electrode active material layer arranged on the surface of the current collector.

[0114] The first positive electrode active material layer is composed of 96wt% polycrystalline lithium manganese oxide, 2wt% acetylene black and 2wt% PVDF, with a gram capacity of 120mAh / g, a thickness of 100μm, and a D50 of the polycrystalline lithium manganese oxide of 15μm.

[0115] Comparative experiment

[0116] A total of 7 groups of samples were taken from Examples 1-6 and Comparative Example 1, with 20 samples in each group. The capacity retention rate of each group of samples was tested for 500 cycles, and the average value of the capacity retention rate was taken for each group of samples.

[0117] The test results are shown in the following table:

[0118]

[0119] According to the above table:

[0120] Compared with Example 1, in Example 2, the proportion of the second positive electrode active material layer increases, the proportion of the first positive electrode active material layer decreases, the manganese ions dissolved from the first positive electrode active material layer decreases, the ability of the second positive electrode active material layer to intercept manganese ions increases, and the overall cycle retention rate is improved.

[0121] Compared with Examples 1 and 2, in Example 3, the proportion of the second positive electrode active material layer increases, the proportion of the first positive electrode active material layer decreases, the manganese ions dissolved from the first positive electrode active material layer decreases, the ability of the second positive electrode active material layer to intercept manganese ions increases, and the overall cycle retention rate is improved.

[0122] It can be seen from Examples 1-3 that when the thickness ratio of the second positive electrode active material layer increases, the overall cycle retention rate of the battery will also increase accordingly.

[0123] Compared with Example 2, the proportion of the second positive electrode active material layer in Example 4 is reduced, but the composite electrolyte layer is added, and the overall cycle retention rate of the battery is significantly increased, which indicates that the electrolyte layer has the effect of intercepting manganese ions, thereby increasing the cycle retention rate.

[0124] Compared with Example 2, the thickness ratios of the first positive electrode active material layer and the second positive electrode active material layer in Example 5 are the same, but the binders are different. The overall cycle retention rate of the battery in Example 5 decreases. The binder in Example 2 is a "mixture of PAA and PAN", and the binder in Example 5 is "PVDF". Since PVDF does not contain functional groups such as hydroxyl and carboxyl, and the "mixture of PAA and PAN" in Example 2 contains hydroxyl and carboxyl groups that can capture manganese ions, thereby preventing manganese ions from moving to the negative electrode and affecting the battery performance, the overall cycle retention rate of the battery in Example 2 is higher than that in Example 5.

[0125] Compared with Example 4, the proportion of the second positive electrode active material layer in Example 6 is significantly increased, but the thickness of the composite electrolyte coating is reduced, and the overall cycle retention rate of the battery in Example 6 is reduced. This shows that the composite electrolyte coating can effectively intercept manganese ions.

[0126] Compared with Examples 1-3 and Example 5, Comparative Example 1 does not have the second positive electrode active material layer, and the overall cycle retention rate of the battery is significantly reduced, which indicates that the second positive electrode active material layer can effectively intercept manganese ions.

[0127] It should be pointed out that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A composite positive electrode sheet, characterized in that: including a current collector, a first positive electrode active material layer and a second positive electrode active material layer; The first positive electrode active material layer is disposed on at least one surface of the current collector, and the second positive electrode active material layer is disposed on a surface of the first positive electrode active material layer away from the current collector; The first positive electrode active material layer comprises a first positive electrode active material, and the second positive electrode active material layer comprises a second positive electrode active material; Wherein, the first positive electrode active material is polycrystalline lithium manganese oxide; and the second positive electrode active material is single crystal lithium manganese oxide.

2. The composite positive electrode sheet according to claim 1, characterized in that: The gram capacity of the first positive electrode active material layer is 120 mAh / g to 130 mAh / g; The second positive electrode active material layer has a gram capacity of 90 mAh / g to 100 mAh / g.

3. A composite positive electrode sheet according to claim 2, characterized in that: The thickness of the first positive electrode active material layer is 60% to 80% of the composite positive electrode sheet. The thickness of the second positive electrode active material layer is 15% to 38% of the composite positive electrode sheet.

4. The composite positive electrode sheet according to claim 1, characterized in that: The polycrystalline lithium manganate D50 range is 6.0 μm to 18.0 μm; The D50 range of the single crystal lithium manganese oxide is 4.0 μm to 18.0 μm.

5. The composite positive electrode sheet according to claim 1, characterized in that: The second positive electrode active material layer further includes a binder; The binder contains hydroxyl groups and / or carboxyl groups in its molecular formula.

6. A composite positive electrode sheet according to claim 5, characterized in that: The binder includes PAA and / or PAN.

7. A composite positive electrode sheet according to any one of claims 1 to 6, characterized in that: Also included is a composite electrolyte layer; The composite electrolyte layer is disposed on a surface of the second positive electrode active material layer away from the first positive electrode active material layer; The composite electrolyte layer comprises nanofibers and a solid electrolyte; The nanofibers are uniformly dispersed in the composite electrolyte layer. Preferably, the nanofibers include polyacrylonitrile fibers modified by -NH2 grafting.

8. A composite positive electrode sheet according to claim 7, characterized in that: The solid electrolyte is water-soluble polyurethane; The water-soluble polyurethane and the polyacrylonitrile fiber are combined by dispersing the polymer solution and the polyacrylonitrile fiber after blending.

9. A composite positive electrode sheet according to claim 8, characterized in that: The composite electrolyte layer also includes lithium salt, and the ion conductivity of the composite electrolyte layer is (6.0)×10-5S·cm -1 .

10. A composite positive electrode sheet according to claim 9, characterized in that: The thickness of the composite electrolyte layer is 2% to 5% of the thickness of the composite positive electrode sheet.

Citation Information

Patent Citations

  • Electrode and battery

    CN116435460A

  • Composite positive electrode and lithium ion battery

    CN116705984A

  • Composite positive plate and battery

    CN117832398A

  • Positive plate, preparation method thereof and battery

    CN118448569A

  • Positive electrode plate and lithium ion battery

    US20200006767A1